Analisis Filsafat Ilmu tentang Pelaksanaan Vaksinasi Meningitis dan Polio pada Calon Jamaah Umrah dalam Perspektif Keperawatan - Pratiwi, Luthi; Siti Rahmalia Hairani Damanik; Amalia Yunita; Etra Fianus Hendri; Mutiara Pertiwi; Suhud (IKES Payung Negeri Pekanbaru, 2025)
Meningitis and polio vaccination are essential requirements for Umrah pilgrims to prevent the transmission of infectious diseases in large-scale gatherings, yet pilgrims’ interpretations of vaccination remain varied and are influenced by their knowledge and religious values. This study aims to explore the meaning of vaccination from the perspective of the philosophy of science through the dimensions of ontology, epistemology, and axiology. Using a reflective qualitative approach, the study involved ten Umrah pilgrims who had undergone vaccination at Klinik Pratama UES Medika Pekanbaru. Data were collected through in-depth interviews and analyzed using reflexive thematic analysis. The findings reveal three patterns of meaning: an existential–spiritual meaning that views vaccination as an effort to maintain health and prepare for worship; a mixed meaning that combines administrative requirements with health-related intentions; and a minimal meaning that regards vaccination merely as a technical procedure. Pilgrims’ knowledge was shaped by information received from travel agencies, healthcare workers, and additional clarification from medical and religious sources, while moral values and social responsibility influenced most participants’ attitudes toward vaccination. The integrity of healthcare workers was also considered important, particularly regarding the refusal to issue vaccination certificates without administration. This study concludes that pilgrims’ vaccination experiences reflect an interplay of existential meaning, knowledge formation, and moral values, with nurses playing a central role through holistic education that is sensitive to religious values and grounded in professional ethics.